RANCANGAN KAWASAN PANTAI DENGAN KONSEP PENATAAN LIMA ZONA - Paramadhyaksa, I.N.W.; Perdanaputra, A.; Permana, I.M.A.; Ariawan, I.K.; Wicaksana, K.P.; Putri, M.S. (Buletin Udayana Mengabdi; Vol 23 No 1 (2024): Buletin Udayana Mengabdi, 2023)
Kelan Beach is known as a beach area located in Desa Adat Kelan, famous for its sunset panorama and attractive views such as plane takeoffs and the Garuda Wisnu Kencana statue. The beach is also supported by the relatively safe waves and the local fishing activities and seafood culinary activities. With the establishment of Desa Adat Kelan as tourist attraction, coupled increasing tourism activities, there are some issues related to spatial planning, visitor vehicle circulation, security, parking areas, and building visualization. Kuliah Kerja Nyata Tematik (KKN-T) Team from the Architecture Study Program of the Faculty of Engineering, Universitas Udayana, proposed a plan to arrange the area into five main zones in order to support sustainable tourism development. The method used is qualitative, with data collection through observation, interviews, and institutional studies, and processing through SWOT analysis. The results of this activity are the arrangement of five zones consisting of Melasti zone, entrance and parking area, cafes and stalls, jukung docking, and recreation, accompanied by arrangements related to security, comfort, and visual aesthetics of the beach area. Keywords: Kelan Beach, zone area, tourism activities, arrangement, plan.